Unveiling sustainable nano-enabled phase change materials for high thermal stability and energy storage capacity. (April 2023) - Atinafu, Dimberu G.; Yun, Beom Yeol; Wi, Seunghwan; Chang, Seong Jin; Kim, Sumin
Abstract: Thermal energy storage and conversion within phase change materials (PCMs) rely on the addition of supporting materials, such as nanomaterials, to improve leakage resistance and heat transfer properties. However, as the supporting fillers obtained from different sources and synthesis methods, the development of renewable and sustainable phase-change composites has received increasing attention in recent years. Here, we develop a phase change composite and adopt Ashby material selection alongside life-cycle assessment to compare and demonstrate the sustainability of different nano-enabled PCMs. The report considers both the environmental impact, economic feasibility and functional performance, including thermal conductivity and energy storage density. The assessment shows that biochar, a biomass derived carbon at low pyrolysis temperature, supporting paraffin composites shows an encapsulation efficiency of >50 %, high shape stability/leakage-resistance capability, suitable cumulative energy demand (100–1000 MJ/kg), and the lowest price (43.00 $/kg with one volume concentration) and price-performance ratio (0.48 $/kJ) In addition, the phase change composite exhibited high chemical compatibility with paraffin, high leakage-resistance (above the pristine phase change temperature at 50 °C) and lowest thermal conductivity (<0.4 W m −1  K −1 ) compared with other carbon-based phase change composites, such as graphene and carbon nanotubes supported paraffin, which is desirable and demanding for practical integration in insulation and building thermal energy management applications and can be used as an alternative carbon-negative sustainable phase change composite to reduce dependence on mineral-based construction materials. Highlights: Sustainable and multidirectional nanocomposite phase change materials. The nanocomposites shows high thermal conductivity and latent heat retention capacity. The biochar-based composite demonstrate an encapsulation efficiency of >50 %. Biochar-based composite showed lowest price (43.00 $/kg) and price-performance ratio (0.48 $/kJ).